Growth slowdowns and role of government linked companies (GLCs) in Malaysia - Kumaran, Vikniswari Vija; Abdullah, Hussin; Hussin, Fauzi (American Scientific Publishers, 2015)
Growth slowdown is a period of stagnation or recession that represents the substantial deviation of a country due its previous norm in term of interest.It will bring interest to policy makers and usually these slowdowns will bring anxiety to middle income countries.The purpose of this study is to examine growth slowdowns and the role of GLCs in contributing to Malaysia GDP. The structure of the reporting will be based on three main topics, growth slowdowns, GLCs efficiency and relationship existence among technical efficiency and GDP growth.The analysis will firstly look into the growth slowdowns and structural break. Secondly, data envelopment analysis will be used to measure the efficiency and finally Granger causality test were conducted to ensure the relationship among the variables on GDP especially technical efficiency of GLCs.